COMPARISON PROBLEM SOLVING MATHEMATICS STUDENTS JUNIOR HIGH SCHOOL IN CIMAHI CITY BETWEEN USING MURDER COLLABORATIVE LEARNING MODEL WITH USING A SAINTIFIC APPROACH - Efendi, Aip Syarif Hasan ((JIML) JOURNAL OF INNOVATIVE MATHEMATICS LEARNING, 2018)
This research is motivated by the low ability of solving mathematical problems of junior high school students towards mathematics subjects. This study aims to find out whether the problem solving ability of junior high school students using MURDER Collaborative Learning Model is better than the students who use the Scientific Approach. Method in this research is experiment. The population in this study is all students of class VIII SMP Negeri in Kota Cimahi. The sample was taken by random class, from 13 classes obtained two classes, namely VIII-B as experimental class I and class VIII-C as experiment class IIl. The experimental class I used the MURDER Collaborative Learning Model, while the experimental class II used the Scientific Approach. Research data obtained through the instrument in the form of data pretest and postest mathematical problem solving ability. The data were processed by normality test, homogeneity test, and test of difference of two mean using Minitab 17 software. The results showed that the ability of solving mathematical problems of junior high school students using MURDER Collaborative Learning Model is better than students using the Scientific Approach.